Ternary cocktail nanoparticles for sequential chemo-photodynamic therapy - Li Fan; Saisai Zhao; Qian Yang; Jiali Tan; Chaojun Song; Hong Wu (Journal of Experimental & Clinical Cancer Research, 2017)
Abstract Background Previous clinical trials have already demonstrated that combinations of two or more drugs were more effective in the cancer treatment, especially sequential photodynamic design combing with sequential chemotherapy. In our study, we propose a ternary cocktail NP delivery system based on self-decomposable NPs, which could realize synergistic chemo-photodynamic therapy through double loading chemo-drugs and multi-level programmable PDT treatment. Methods PS drug methylene blue (MB) was encapsulated into the center of the NPsmall, NPbig&thin, and NPbig&thick carriers through “grown-in” loading mechanism, which was released based on the drug concentration difference of the drug release environment. NPsmall, NPbig&thin, and NPbig&thick carriers have three different drug release profiles, which could realize multi-level programmable PDT treatment. At the same time, antitumor drug gemcitabine hydrochloride (GM) and Docetaxel (DTX), were chosen as the double loading chemo-drugs that absorbed onto the NPbig&thin and NPbig&thick surface, respectively. In specific, various particle configurations were used for modulating the inner MB sequential release with three pulse Tmax. Also, by adjusting the NPbig&thin and NPbig&thick configuration, the release interval lag time between absorbed GM and DTX can be successfully modulated to achieve maximized chemotherapeutic efficacy. Results In vitro and in vivo results demonstrated that these three pulses Tmax and the sustained release of MB could maximize the multi-level programmable PDT treatment. And the absorbed GM and DTX also have a release time lag of 12 h, which has been proved as the most effectiveness synergistic interval lag time in the cancer treatment. Conclusion Such a precise sequential release manner ternary cocktail NPs provided a promising platform for efficient and safe chemo-photodynamic therapy, which serves as a promising drug delivery system to cure cancer in the future.